Study of the Electrochemical Behavior of Merocyanine and Merocarbocyanine Salts and Their Transformation into Π-Electron Donor Molecules, Namely Tetrathiatetraazafulvalenes - Manel Khiat; Fatima-Zohra Zradni; Souad Kasmi-Mir; Alejandro Baeza (Universitas Gadjah Mada, 2021)
An electrochemical study using the cyclic voltammetry method was carried out on some previously prepared merocyanines salts, namely thiazolideniumsulfonate salts 5a-b, and thiazolidenium chloride salts 6a-b, and merocarbocyanines salts, namely alkylidenthiazolidenium sulfonate salt 5c, and alkylidenthiazolidenium chloride salt 6c. These salts are transformed by dimerization in situ in a voltammetric cell into tetrathiatetraazafulvalenes (TTTAFs) 7a-b, 7’a-b, 8c, and 8'c supposed to be π-electron donor molecules due to the existing conjugation in their structure. The structure of all new chemically synthesized molecules was confirmed by IR, 1H-NMR, 13C-NMR, and MS. The transformation of salts into TTTAF was confirmed by a reversible voltammogram curve and the variation of observed potentials.